An assessment of positions, perceptions and valued leadership competencies of pharmacists that work in manufacturing pharmaceutical companies (MPCs) in South Africa - Nsovo Mayimele; Patrick Demana; Mothobi Keele (SocioEconomic Challenges, 2023)
Pharmacists are custodians of medicines and play a significant role in the healthcare system as the profession responsible for managing medicines. A self-administered online questionnaire was distributed to pharmacists who are members of the South African Association for Pharmacists in Industry (SAAPI). A majority (66%) of responses received was from females, 87.9% identified experience as the attribute necessary for pharmacists to enter positions of strategic leadership as opposed to availability of opportunities (69.7%) and having an additional business-related qualification (60.6%). Pharmacists that work in the manufacturing sector of the industry were mostly working at technical levels. They were in positions such as responsible pharmacist (RP) (24,1%, n=66), regulatory affairs (18,5%, n=66), quality assurance (16,7%, n=66) production (11,1%, n=66) pharmacists. The pharmacists felt that experience was the key attribute required for entry into strategic leadership positions of manufacturing pharmaceutical companies (MPCs), the attribute for possessing business-related qualifications followed this. The need for a quota system that makes provision for a pharmacist to be present in certain strategic leadership positions of an MPC, was supported by respondents (58%, n=66), 91% of the respondents deemed it necessary for all MPCs to have a pharmacist in the strategic leadership of MPCs. The presence of pharmacists in the strategic leadership of MPCs was limited. The pharmacists who participated in the study felt that their presence could add value as strategic leaders of MPCs.
Keywords: I11; P46; L65; 330; Leadership competency; pharmacists; industrial pharmacy; manufacturing pharmacy; strategic leadership; pharmacists